Management of avulsed tooth having extra oral dry time more than 48 hours: a case report - Tomar, Sachin; Thakur, Seema (International Journal Of Community Medicine And Public Health, 2025)
Tooth avulsion is one of the most common type of dental traumatic injuries which is one of main reason of loss of teeth. Loss of tooth causes aesthetic and functional problems in which the patient is not only affected physically, but socially or psychologically also. If extra oral dry time exceed 60 minutes’ prognosis of treatment, then prognosis of replantation becomes very poor. In this case report, we discussed about delayed replantation of avulsed tooth. After the clinical examination, extra oral root canal treatment was done and tooth is placed in sodium fluoride solution for 20 minutes and then dexamethasone immediately before procedure then platelet‐rich fibrin (PRF) is placed in socket and tooth is replanted into the socket and flexible splint is placed from canine to canine for 4 weeks. The patient was re-evaluated in the subsequent follow-up, the patient was asymptomatic with favourable soft tissue healing and good aesthetics. This case report includes proper history taking, diagnosis, and treatment of avulsion by delayed replantation in order to maintain the tooth in arch and preserve the alveolar bone.